PENGARUH MEDIA PEMBELAJARAN POWERPOINT INTERAKTIF TERHADAP CARA BERKOMUNIKASI SOSIAL DALAM PEMBELAJARAN IPS KELAS 4 SD NEGERI 011 DUMAI - Hayatun Nufus; Muhamad Nukman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this research is to find out whether interactive PowerPoint material has an impact on social communication in grade 4 social studies learning at SD Negeri 011 Dumai. With a one-group pretest-posttest design, this research is included in the pre-experimental design research category. The research participants were class 4 students at SD Negeri 011 Dumai with a total of 40 students, namely class 4A and 4B at SD Negeri 011 Dumai. Purposive sampling was used to determine the sample. Research findings show that PowerPoint learning media has a significant influence on the way of social communication. Thus, it can be said that the social communication strategies of grade 4 students at SD Negeri 011 Dumai are greatly influenced by the use of interactive PowerPoint materials in social studies classes.